Hierarchically Distributed Energy Management in Distribution Systems: An Error-Tolerant and Asynchronous Approach - Su, Yifan; Wu, Shiyong; Wang, Zhaojian; Bao, Zhiyuan; Liu, Feng (IEEE transactions on smart grid, 2024)
Distribution systems are becoming more complex with the integration of numerous distributed energy resources (DERs), such as distributed generators (DGs), distributed energy storages (DESs), and controllable end-users (EUs). Aggregators (Aggs) are emerging to bridge the gap between the distribution system operator (DSO) and EUs. This creates a hierarchical "DSO-Agg-EU" architecture that requires effective and efficient coordination among massive agents. However, this architecture faces challenges such as communication asynchrony and solution inexactness among different agents, which may undermine the performance of energy management or even cause unexpected failures. To address these challenges, this paper proposes an error-tolerant and asynchronous algorithm based on dual decomposition for hierarchically distributed energy management (HDEM). The algorithm is theoretically guaranteed to converge to a near-optimal value and can be further accelerated by Nesterov's method. The algorithm is tested on the IEEE 123-bus distribution system and demonstrates high effectiveness and efficiency under asynchrony and inexactness.